Defining Modernity through Education: Women’s Responses from Colonial Punjab - Minocha , Arti (South Asian Journal of Social Sciences and Humanities, 2022)
Late-19th and early-20th centuries in Punjab were times of ferment and formation of new class, caste, gender, and religious identities. The quest for a localized modernity at this historical juncture was spear-headed by reform movements of Arya Samaj, Singh Sabha, and Ahmaddiya reform movement, that predicated their quest on the construction of ‘modern womanhood’. The new technology of print was used effectively by reform patriarchies to disseminate these representations of modern womanhood. While much has been written about these patriarchal reform movements that projected their own modernity through ‘liberal improvements’ in the condition of their women and by opening up to ideas of education and companionate marriages, the presence of women in this history has been elided over. This essay examines the print spheres in late-19th and early-20th century Punjab, especially the periodical press, to trace women’s responses to reform prescriptions about their education and deportment. It is in this interplay between dominant discursive formations and alternative modes of articulation by women that multiple cultural meanings emerge.